2017
DOI: 10.17816/vto20172436-13
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Correction of Spine Deformity in Patients with Spinal Muscular Atrophy: Multicenter Analysis of Domestic Experience and Literature Review

Abstract: Purpose: to analyze the domestic experience in surgical correction of spine deformity in patients with spinal muscular atrophy (SMA). Patients and methods. Retrospective multicenter nonrandomized study (evidentiary level III) was performed. Treatment results were analyzed for 26 patients aged 6 - 25 years who were operated on at four RF centers. Inclusion criteria: patients with neurogenic scoliosis on a background of SMA, genetically confirmed diagnosis of type II and III SMA, frontal-plane Cobb angle over 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…4 Most studies show improvement in the quality of patients' and caregivers' life and caregivers' satisfaction. [23][24][25][26] They found that most of the patient caregivers felt that those patients treated surgically were more comfortable than those who were not. Not all research results demonstrated significant changes in the quality of life of the patients or improvement in vital signs.…”
Section: Nms Group MD (N=13) Sma (N=12) Dmd (N=14) Cp (N=32) Total (N...mentioning
confidence: 99%
“…4 Most studies show improvement in the quality of patients' and caregivers' life and caregivers' satisfaction. [23][24][25][26] They found that most of the patient caregivers felt that those patients treated surgically were more comfortable than those who were not. Not all research results demonstrated significant changes in the quality of life of the patients or improvement in vital signs.…”
Section: Nms Group MD (N=13) Sma (N=12) Dmd (N=14) Cp (N=32) Total (N...mentioning
confidence: 99%